2010
DOI: 10.1111/j.1755-148x.2010.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphologic features for melanoma classification

Abstract: Summary Melanoma is comprised of biologically distinct subtypes. The defining clinical, histomorphologic and molecular features are not fully established. This study sought to validate the association between genetic and histomorphologic features previously described, determine their reproducibility, and association with important clinical variables. Detailed clinical and histomorphologic features of 365 primary cutaneous melanomas were assessed by 11 pathologists and correlated with mutation status of BRAF an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
128
7
15

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 19 publications
11
128
7
15
Order By: Relevance
“…Some studies have shown that this mutation is prevalent in younger patients (Goel et al, 2006;Liu et al, 2007;Broekaert et al, 2010;Hacher et al, 2010;Menzies et al, 2011;Long et al, 2011). However, this association was not confirmed in the metaanalysis by Lee et al (2011) or in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…Some studies have shown that this mutation is prevalent in younger patients (Goel et al, 2006;Liu et al, 2007;Broekaert et al, 2010;Hacher et al, 2010;Menzies et al, 2011;Long et al, 2011). However, this association was not confirmed in the metaanalysis by Lee et al (2011) or in the present study.…”
Section: Discussioncontrasting
confidence: 56%
“…BRAF-mutant melanoma is associated with younger patient age, lack of CSD at the primary site, truncal location, high body nevus counts, and certain pathologic characteristics (12,13,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Just as BRAF wild-type and mutant melanoma have differing clinicopathologic features, we hypothesized that the mutant genotypes are also distinct.…”
Section: Introductionmentioning
confidence: 99%
“…Many aggressive melanomas, including BRAF V600E melanomas, maintain differentiation characteristics in situ (Broekaert et al, 2010;Ohsie et al, 2008).…”
Section: Introductionmentioning
confidence: 99%